Education Management Strategies to Face Challenges and Opportunities in The Digital Age - Nisa Utami, Vani Qhairum; Rusdinal, Rusdinal; Hadiyanto, Hadiyanto (International Journal of Educational Dynamics, 2023)
The Digital Age brings many changes to the function of education, one of which is the leadership and role of the principal six who must adapt to the needs of the new era. The purpose of this research is to find out the principal's leadership style in facing the Fourth Digital Era from an educational management perspective. This research adopts a phenomenological perspective and qualitative research methodology. data collection procedures include observation, interviews, and research notes. In one of the private schools in Surabaya, the research informants consisted of 6 principals and 1 supervisor. The research findings show that a democratic leadership style is adaptive to change and principals need to develop new knowledge and skills in the era of the fourth industrial revolution, particularly in the areas of technology use and entrepreneurship.